Technical and Economic Synergetic Effect in Conditions of Innovative Transformation of Water Supply and Sewerage Economy - Kalyuzhniy, Anatoly; Zubrycheva, Lyudmyla; Savyk, Vasyl (International Journal of Engineering and Technology, 2018)
There has been conducted a study of interdependence between technical and economic researches of diameters calculation of water pressure supply and sewerage networks. There has been offered the method to calculate the optimal diameter of water pressure supply and sewerage networks made of polymeric pipes. This qualitative and quantity methodology includes, firstly, the observation review of Ukrainian water supply and sewerage networks and, secondly, the survey of financial and economic documents of water supply and sewerage economy. The factual basis of the study is the initial data of statistical monitoring of work conditions of water pressure supply and sewerage networks. The paper proposes using the net present value (NPV) to calculate the optimal diameter of water pressure pipes made of polymeric materials, which, finally, decreases capital and exploiting expenditures and considers the maximum income for water supply and sewerage economy (WSE).Â